Elevated temperature tensile properties of a ternary eutectic Al–27%Cu–5%Si cast alloy - Samuel A. Awe (International Journal of Lightweight Materials and Manufacture, 2021)
Eutectic alloys have several advantages when compared to single-phase systems. Moreover, the solidification characteristic and microstructural features of eutectic alloys have continued to gain more attention in recent years due to their impact on the properties and performance of such eutectic materials. In this study, a eutectic Al–27%Cu–5%Si ternary alloy was investigated to understand its microstructural formation and its influence on the hardness and high-temperature tensile properties of the alloy. The eutectic composite was produced through a rapid solidification technique and its microstructure characterized by an optical microscope as well as a scanning electron microscope coupled with energy dispersive spectrometry (SEM-EDS). The hardness of as-cast alloy was evaluated at room temperature while its tensile properties were investigated at temperatures ≤400 °C. The results revealed that the cast alloy consists of both binary and ternary eutectic microstructures with different length-scales, which has considerably contributed to the mechanical performance of the eutectic composite up to 300 °C when compared to the traditional Al–Si (A319) cast alloy. The alloy displays a high hardness value of 224HV and a relatively higher elevated-temperature tensile strength of 217 MPa at 300 °C. The tensile strengths of the ternary eutectic alloy are 54% and 139% higher than that of the reference A319 casting alloy at temperatures of 200 °C and 300 °C, respectively.